Answer: -3
Step-by-step explanation:
Since we are given the value of r, we can plug that value into the expression and solve.
15+6(-3) [multiply]
15-18 [subtract]
-3
Now, we know that the expresison is equal to -3.
Answer:
75+x?
Step-by-step explanation:
7 + 2(x - 3) + 5x
= 7 + 2x - 6 + 5x <em>distributed 2 into x - 3</em>
= 7 - 6 + 2x + 5x <em>grouped like terms together</em>
= 1 + 7x
You didn't provide an image of the steps but hopefully you can figure it out based on the information I provided.
Answer:
yes ?-?
Step-by-step explanation:
I would assume this to be equal to y⁴ ₓ y⁵
= y⁴ ⁺ ⁵, By law of indices.
= y⁹
I hope this helped.